2007
DOI: 10.1016/s1472-6483(10)61049-8
|View full text |Cite
|
Sign up to set email alerts
|

TSPY gene copy number as a potential new risk factor for male infertility

Abstract: The human TSPY (testis-specific protein, Y-linked) gene family (30-60 copies) is situated in the MSY (male-specific) region of the Y chromosome. Testis-specific expression indicates that the gene plays a role in spermatogenesis. Refined quantitative fluorescence PCR (polymerase chain reaction) was applied to evaluate the relative number of TSPY copies compared with AMELY/X (amelogenin gene, Y-linked) genes in 84 stratified infertile men and in 40 controls. A significantly higher number of TSPY copies was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 35 publications
2
52
0
Order By: Relevance
“…2). Although copy number varies among individuals within a range of 11 to 76 (26,50,51), the majority of men (about 65 % of the Italian population) remain within a restricted interval (21 to 35 copies) (47). The evolutionary conservation of multiple TSPY1 copies on the Y chromosome of other mammals as well as the above mentioned limited variation in copy number in humans suggest that a minimum TSPY1 copy number is likely to be maintained through selection (52).…”
Section: Tspy1 Arraymentioning
confidence: 99%
See 1 more Smart Citation
“…2). Although copy number varies among individuals within a range of 11 to 76 (26,50,51), the majority of men (about 65 % of the Italian population) remain within a restricted interval (21 to 35 copies) (47). The evolutionary conservation of multiple TSPY1 copies on the Y chromosome of other mammals as well as the above mentioned limited variation in copy number in humans suggest that a minimum TSPY1 copy number is likely to be maintained through selection (52).…”
Section: Tspy1 Arraymentioning
confidence: 99%
“…The evolutionary conservation of multiple TSPY1 copies on the Y chromosome of other mammals as well as the above mentioned limited variation in copy number in humans suggest that a minimum TSPY1 copy number is likely to be maintained through selection (52). Only few studies have focused on the eventual TSPY1 influence on spermatogenesis and frustratingly they all reached three different conclusions, probably due to study design biases (26,50,51). Indeed, crucial for a reliable analysis is the TSPY1 copy number variation susceptibility to stratification biases.…”
Section: Tspy1 Arraymentioning
confidence: 99%
“…According to Vodicka et al 27 , there is also a potential correlation between impaired fertility in males and the TSPY gene copy number. The relative number of copies is higher in infertile men, with the exception of the AZFa deletion case 27 . Giachini et al 34 , found that the TSPY gene copy number affects spermatogenesis and that low copy number is a factor contributing to male infertility.…”
Section: Discussionmentioning
confidence: 87%
“…Vodicka et al (2007) assessed the relative number of TSPY copies by RQF-PCR in an infertile group (84 cases) and in 40 controls, and found an association of higher number of TSPY copies with impaired sperm production. Nickkholgh et al (2010) compared the absolute TSPY copy numbers by quantitative PCR and Southern-Blot analyses in selected cases of 100 men with idiopathic infertility versus 100 normozoospermic controls, and found no association between TSPY copy number and the fertility status.…”
Section: Male Idiopathic Infertilitymentioning
confidence: 99%